Risking delay: the storylines of (bioenergy with) carbon capture and storage in Swedish parliamentary discourse - Almqvist-Ingersoll, Ashley (Frontiers in Climate, 2025)
Carbon Capture and Storage (CCS), along with Bioenergy with Carbon Capture and Storage (BECCS), feature heavily in climate mitigation scenarios. Nevertheless, the technologies remain controversial within the broader mitigation discourse, in part for their potential to excuse delay in more ambitious emissions reductions in the short term. Sweden has included BECCS and CCS as proposed “supplementary measures” to enable the country to meet its ambitious target of achieving net negative emissions by 2045. Hajer’s Argumentative Approach to Discourse Analysis is applied to Swedish parliamentary speeches, motions, and written questions and answers, to uncover the storylines and attendant assumptions constituting Swedish policy deliberation regarding CCS and BECCS. This study finds that by problematizing climate change as an issue of emissions, actors position CCS and BECCS within a dominant neoliberal discourse and characterize them as tools to facilitate a green transition centering on industrial and economic competitiveness. This discourse lacks detail, and risks delay by oversimplifying the needs and requirements for CCS and BECCS deployment. Meanwhile, a CCS-critical discourse acknowledges the need for negative emissions but challenges storylines portraying the technology as inexpensive or easy to deploy rapidly. If pursued, this discourse could serve to sharpen the debate about the technologies and bring planning in line with aspirations, helping to avert risks of delay.